Development of hotel yield management and reservation for hotels in Sarawak / Lincoln Philip Mujah - Lincoln, Philip Mujah (2007)
This project presents development and implementation of a centralized yield management project by an international hotel group in it's over 14 hotels in Sarawak- Data were collected from the participant hotel group's three management levels through semi-structured interviews, observations and document analysis. The research findings reveal that developing and implementing a centralized yield management project is contextually a very helpful in pricing strategy. Major problems and difficulties using numeric report are solved using the new report trend that is graphical report